Case report: Hepatic tuberculosis mimicking hepatocellular carcinoma in a patient with cirrhosis induced by hepatitis B virus - Hu, Na; Wu, Yuhui; Tang, Maowen; Luo, Tianyong; Yuan, Shengmei; Li, Cai; Lei, Pinggui (Frontiers in Medicine, 2022)
Hepatic tuberculosis, secondary to post-hepatitis B cirrhosis, is extremely rare. We report a 69-year-old man with post-hepatitis B cirrhosis complicated by primary isolated hepatic tuberculosis who was initially misdiagnosed as having hepatocellular carcinoma (HCC). The patient was hospitalized with complaints of two weeks of fever. He had a 20-year history of post-hepatitis B cirrhosis. The laboratory tests suggested that his serum alpha-fetoprotein (AFP) level was markedly elevated to 1210.00 ng/mL. Abdominal ultrasound (US) and magnetic resonance imaging (MRI) confirmed cirrhosis and discovered a space-occupying lesion of the hepatic left lobe as well as portal vein filling defects. These results led us to consider primary liver cancer and portal vein tumor thrombus combined with decompensated cirrhosis. Biopsy and histology may be considered the ultimate diagnostic tests, but needle biopsy was refused because of his high risk of bleeding as well as the patient had declined the offer. To cope with his fever, the patient was given broad-spectrum antibiotic treatment initially, followed by intravenous vancomycin. After antibiotic treatment failed, the patient was treated with anti-tuberculosis for ten days; after that, the patient maintained a normal temperature. The patient continued to receive tuberculostatic therapy for six months following his discharge. AFP completely returned to the normal level, and the aforementioned mass disappeared. Finally, hepatic tuberculosis secondary to post-hepatitis B cirrhosis with portal vein thrombosis (PVT) was considered to be the final diagnosis. More than two imaging techniques discover a space-occupying liver lesion and that the serum alpha-fetoprotein (AFP) level is extremely elevated, which means that hepatocellular carcinoma (HCC) could be diagnosed. However, some exceedingly rare diseases should not be excluded. This case illustrated that the non-invasive diagnostic criteria for liver cancer might be considered carefully when discovering a space-occupying lesion of the liver in a patient with cirrhosis and elevated AFP. Instead, primary hepatic tuberculosis should be considered and included in the differential diagnosis, and a biopsy should be performed promptly.